2014
DOI: 10.1007/s10841-014-9740-7
|View full text |Cite
|
Sign up to set email alerts
|

Species conservation under future climate change: the case of Bombus bellicosus, a potentially threatened South American bumblebee species

Abstract: Bees ensure 35 % of global food production, but this service is endangered due to several threats. Declines in bumblebee populations (genus Bombus) have been reported worldwide. Bombus bellicosus is one of the rare cases of reported threatened bumblebees in South America. It was once widespread in southern Brazil's grasslands until the 1960s. During that time, that area underwent increasing land use which led to a decrease in bee abundance and richness, and to local disappearance of B. bellicosus. Climate chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 87 publications
7
32
2
5
Order By: Relevance
“…nigrita are highly plausible across a range of climatic scenarios. We discuss bionomic features of this species that may be responsible for its predicted robust response to climate change, in contrast with extensive range contractions predicted for other bees (Giannini et al 2012;Rasmont et al 2015;Martins et al 2015).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…nigrita are highly plausible across a range of climatic scenarios. We discuss bionomic features of this species that may be responsible for its predicted robust response to climate change, in contrast with extensive range contractions predicted for other bees (Giannini et al 2012;Rasmont et al 2015;Martins et al 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Although previous studies using SDMs already showed that the range sizes of some South American bees from the genera Melipona, Centris, Xylocopa, and Bombus (Giannini et al 2012(Giannini et al , 2013Martins et al 2015) may decrease their range sizes in response to future climate changes, such negative responses may not be general. Certain habitat generalist species, especially thermophiles, may benefit from future climate change, expanding their range to currently unsuitable areas.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We georeferenced the localities using the point-radius method (Wieczorek et al 2004). The methods we used were described elsewhere in previous studies (i.e., Silva et al 2014aSilva et al , b, 2015Martins et al 2015). Briefly, we applied a principal components analysis to the 19 variables from Worldclim to generate 19 orthogonal principal components (PCs hereon; Table S1, supplementary material), from which we considered the first 4 (∼90 % of the original climatic variation) to predict the distribution for C. merrillae .…”
Section: Potential Distribution Modelmentioning
confidence: 99%
“…A recent study shows that the suitable climatic conditions for another South American temperate bumblebee species (B. bellicosus) will retreat southwards under future climate scenarios (Martins et al 2014). Although climate warming might play a role in the southward retraction of B. dahlbomii (Morales et al 2013), this alone cannot explain the speed and timing of the species collapse.…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%